2007
DOI: 10.1111/j.1540-5885.2007.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Use and New Product Outcomes: The Contingent Role of Strategy Type

Abstract: Information is an important resource for firms to develop new products successfully, and firms must rely on their ability to use information effectively. This research builds on information processing and contingency theories to explore the effect of firm strategy type and the conceptual and instrumental use of information on new product outcomes. Firms operating in high-tech industries are faced with high levels of uncertainty caused by rapidly evolving technologies. Consequently, creating innovative and succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 90 publications
(123 reference statements)
1
50
0
4
Order By: Relevance
“…IU is a critical aspect of information processing since in this stage the acquired information is applied to strategic and tactical outcomes to impact firm performance (Citrin et al, 2007).…”
Section: Information Quality and Information Usementioning
confidence: 99%
“…IU is a critical aspect of information processing since in this stage the acquired information is applied to strategic and tactical outcomes to impact firm performance (Citrin et al, 2007).…”
Section: Information Quality and Information Usementioning
confidence: 99%
“…However, other scholars have suggested that Cronbach's alpha as low as 0.60 are acceptable for hypothesis testing. Moreover, inter item to total correlation values 0.3 or greater is acceptable for data analysis that indicates of the degree (strength) to which each item correlates with the total score [17,[63][64][65][66]]. …”
Section: Empirical Value Reliability Tests Of a Constructmentioning
confidence: 99%
“…Por isso, trabalhar com equipes multidisciplinares é uma condição básica para uma maior integração e visão sistêmica do PDNP (CLARK; FUJIMOTO, 1991;WIND;MAHAJAN, 1997). Propõe-se, então, que: H4: a integração funcional das atividades de DNP é positivamente relacionada ao desempenho do PDNP.…”
Section: Fatores Mercadológicos: a Intensidade Competitiva E O Enfoquunclassified
“…Empresas que buscam apoio externo no DNP estão mais propensas a melhorar seu desempenho no que se refere à inovação, à sua lucratividade e à sua rentabilidade (CALANTONE; STANKO, 2007;HEIRMAN;CLARYSSE, 2007). Isto posto, emerge a hipótese de que: H5: a colaboração com instituições de ciência e tecnologia (C&T) é positivamente relacionada ao desempenho do PDNP.…”
Section: Fatores Mercadológicos: a Intensidade Competitiva E O Enfoquunclassified